The Impact of Constitutional Court Ruled On The 2019 Presidential Election Toward Indonesian Stock Market - Aditya Putra Dewantara; Intan Nurul Awwaliyah; Marmono Singgih (Conference Series, 2020)
The main purpose of this study is to examine the efficiency of the Indonesian capital market as a result of The Impact of Constitutional Court Ruled On The 2019 Presidential Election Toward Indonesian Stock Market. This study uses the event study method with a research period of 7 days before and 7 days after the Constitutional Court ruled on the 2019 presidential election. The data normality test shows that the data is not normally distributed then the research hypothesis uses a non-parametric test, the Wilcoxon Paired Sample test. By using the abnormal return as a variable, the results of the study show that there is no significant difference in the average abnormal return both before and after the Constitutional Courts ruled on the 2019 presidential election lawsuit.